Before You Go: Organizing Family Legal Matters and Finances Prior to Military Deployment - William Parker; Heidi Liss Radunovich (EDIS)
Military members and their families have many things to prepare before deployment, so it is easy to overlook some important issues. This 3-page fact sheet helps military service members and their families take care of their financial and legal matters before deployment. Written by William Parker and Heidi Liss Radunovich, and published by the UF Department of Family, Youth and Community Sciences, June 2012.